The Economic Pressure and Coping Strategy of the Family of Cash Conditional Transfer Recipients - Megawati Simanjuntak (Journal of Family Sciences, 2016)
Cash Conditional Transfer (CCT) or Program Keluarga Harapan (PKH) is one of the attempts of  Indonesian government to alleviate poverty. This study conducted in eight villages in Dramaga District, Bogor Regency for six months. This study aimed to analyze the difference of economic pressure and families coping strategies of economic functions between pre and post the family got CCT’s funds and to analyze the relationship of socioeconomic and demographic characteristics, economic pressure and coping strategies of economic functions. By using systematic random sampling, this study produced 150 samples. Family size, amount of debt, the ratio of debt and assets, and economic pressure significantly and positively correlated with the total coping strategies both in pre and post-CCT. On the other hand, the total coping strategies both in the pre and post-CCT also significantly and negatively correlated with the level education of wives. In addition, the husbands and wives age significantly and positively related to the coping strategies during post CCT, while the total family income correlated significantly and negatively.